Захист приміщень від витоку мовної інформації за допомогою систем віброакустичного зашумлення - Патлан, Є. О. (ХНУРЕ, 2023)
The ways of active protection of premises from the leakage of speech information with the help of vibroacoustic noise systems, as well as issues related to the optimal placement of vibration emitters are considered.
Keywords: виток мовної інформації; віброакустичне зашумлення